Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Badan Pusat Statistik (BPS) - Umaya, Siti Nur; Sudarwadi, Dirarini; Haryati, Ismi (Lensa Ekonomi, 2025)
This research aims to determine the influence of organizational culture on employee performance at the West Papua Province Central Statistics Agency Office. The analysis technique used in this research is quantitative. The sampling technique in this research is saturated sampling with a sample size of 51 respondents. The primary data used is in the form of interviews and questionnaires, the secondary data used is in the form of journals, agency profiles and books used as references. The data analysis technique used is chi-square test analysis with the help of the SPSS version 26 software computer application. Based on the results of the analysis that has been carried out, it can be seen that the calculated chi-square value (0.874) < chi square table (3.481), it can be said that organizational culture has a strong relationship with performance at Central Statistics Agency Office.